MO001THE EUROPEAN DRTA REGISTRY: AN INITIAL DATA ANALYSIS*. (29th May 2021) - Bockenhauer, Detlef; Emma, Francesco; Talhi, Amina; Papizh, Svetlana; Atmis, Bahriye; Homan, Nakisa; Aksu, Bagdagul; Santos, Fernando; Boyer, Olivia; Fila, Marc; Bayrakci, Umut Selda; Ouda Eid, Loai Akram; et al.
Abstract: Background and Aims: Distal renal tubular acidosis (dRTA) is a rare disorder characterised by an inability of the distal tubule to secrete acid, leading to metabolic acidosis. Clinical consequences typically include hypokalaemia, hypercalciuria with nephrocalcinosis and/or urolithiasis, as well as bone disease. Treatment with adequate alkali supplementation corrects the acidosis and hypercalciuria, but there are few data on long-term outcome. In 2018, a registry for dRTA was established by the European Society for Paediatric Nephrology, hosted by the European Rare Kidney Disease Reference Network. Here, we present an initial analysis of data in the registry. Method: Analysis of data entered into the registry by the cut-off data of 18/11/2020. Results: A total of 135 patients had been entered, of which 106 had additional data from an annual follow-up visit. Median age at last visit was 10 years (range 0-54), including 16 adults (>17y). Genetic testing had been performed in 91 subjects and causative variants were reported in 74 (81%). Pertinent clinical details according to genetic group are listed in table 1. Treatment was provided with at least 15 different preparations, containing citrate or bicarbonate, given in 1-10 (median 3) daily doses. Adequate treatment at last follow-up, as judged by a plasma bicarbonate level >21 mmol/l and a urine calcium-creatinine ratio in the age-specific normal range was present in 46% of subjects. There was a trend for higher eGFR and height SDS in subjects with adequate treatment compared to those without, but this was not statistically significant. Conclusion: Currently available data demonstrate the difficulties in treating dRTA, with less than half of subjects achieving adequate control of their acidosis. By collecting long-term data, the registry will provide important information on the prognosis and complications of dRTA and to what degree these can be prevented with treatment. Enrollment of further, especially adult patients will contribute to our understanding of this rare disorder.